Analisis Determinan Struktur Modal Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2016-2022 - Siregar, Uli Rohana; Tanjung, Ahmad Albar; Sukardi, Sukardi (Ekonomis: Journal of Economics and Business, 2024)
The purpose of this study was to analyze the effect of profitability, tangibility, growth opportunity, non-debt tax shield (NDTS), uniqueness on the company's capital structure. The data used in this research is panel data taken from the financial reports of manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange (IDX) from the 2016-2022 period. By using non-probability sampling method with purposive sampling technique, a sample of 20 companies was obtained. The method used is panel data regression analysis method. In this research, testing and selection of the best model was carried out using the Chow test and Hausman test, and the result is that the Fixed effect model is the best model. The results showed that profitability, non-debt taxshield (NDTS) and uniqueness had a negative and significant effect on capital structure, with each value of the coefficient of profitability, non-debt taxshield (NDTS) and uniqueness, tangibility has a positive and significant effect while growth opportunity has a positive and insignificant effect with each tangibility coefficient value, growth opportunity by testing using a significance level of 5%. Simultaneously, profitability, tangibility, growth opportunity, non-debt tax shield (NDTS), uniqueness significantly influence the capital structure with a coefficient of determination of 82.7746%.